Concordance rate amongst electronic databases about drug interactions between warfarin and antimicrobials: a descriptive analysis - Meregall, Rosana Thalia; da Silva Dal Pizzol, Tatiane; Mello de Oliveira, Luciana (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
Drug interactions (DI) are adverse events that may compromise therapeutic effectiveness and patient safety. Warfarin is associated with relevant DI with several drugs, including antimicrobials (AM). Objective: to analyze the degree of agreement between informa-tion on the probable mechanism, classification of severity and suggested management of potential DI between warfarin and AM present in the Municipal List of Medications of Porto Alegre (REMUME/POA), in the electronic databases (EDB) UpToDate®, Drugs.com®, Medscape® and Micromedex®. Methodology: descriptive analysis in accordance with the Guidelines for Reporting Reliability and Agreement Studies. Results: Of the fifteen AM, 13 had reported DI with warfarin in at least one of the four EDB. For the DI classification, the total concordance rate obtained in the four consulted EDB was 33%; Partial agreement between two EDB was 33% and between three, 33% either, and the EDB most in agreement with each other were UpToDate® and Drugs.com® (87%).As for the probable mechanism of the DI, there was no complete agreement between the four BDE; partial agreement between two EDB was 38% and between three, 23%, and the EDB that most agreed with each other were UpToDate® and Medscape® (38%). For the suggestion of clinical management, the total agreement was 23%; partial agreement between two EDB was 38%, and between three, 38%. The most concordant EDB were UpToDate® and Drugs.com® (85%).Conclusions: Total concordance rates between the EDB are relatively low; however, partial agreement is higher